Study on chemical control indicators for circulating cooling systems water chemistry at power plants - Кишневский, Виктор Афанасьевич; Чиченин, Вадим Валентинович (Eastern-European Journal of Enterprise Technologies, 2014)
An analysis of applied stability indices, used for water chemistry control of circulating cooling systems at TPP and NPP is given in the paper. The spectrum of controlled indicators of circulating and make-up water during long-term operation of various water chemistries on scale models of circulating cooling systems at TPP and NPP is investigated. The results of chemical control of water chemistry with dosing mineral acid to make-up water and acrylic water chemistry without dosing mineral acid of the circulating cooling system at the Rivne NPP are given. Estimated efficiency control of water chemistry was performed by the thickness of deposits on the heat exchange surface of condensers and intensity of corrosion on control samples. It is shown that at a given evaporation rate of circulating water and quality of make-up water, and different doses of acrylic inhibitor, the studied controlled parameters of water chemistry of the system remained without any visible changes. Thus, the values of the empirical stability indices and their changes in time cannot be used to estimate the amount and rate of CaCO3 precipitation from solution, and moreover the deposition rate on heat exchange surfaces, which is often used in practice.